Lucky days with Mr. and Mrs. Green - Keith Baker (Orlando, Florida : Harcourt, 2005)
Mr. and Mrs. Green, a loving alligator couple, are back for another round of sweet and adventurous alligator escapades. This time they're trying their hand at detective work, entering a gumball-guessing contest, and (most daring of all!) participating in the town talent show. Happily for the Greens, luck is on their side. Luck and cookies--JUMBO cookies! With its snappy text and warm, bright illustrations, this